An evaluation of open versus laparoscopic cholecystectomy in tertiary centre - Goel, Kanwar Singh; Goel, Sapna; Singla, Sham L.; Tiwari, Pawan (International Surgery Journal, 2019)
Background: Cholecystectomy is a method of treatment for acute or chronic cholecystitis with cholelithiasis or any other diseases of gall bladder. The diagnosis of gall stone disease depends on an accurate history, physical examination, supporting lab investigations and a proper ultrasound of abdomen. After the advent of lap cholecystectomy there is revolution in minimally invasive surgery. Because of better technological innovations, the lap cholecystectomy has become gold standard presently. Methods: This prospective observational study was performed in Surgery Department in SGT Medical College, Budhera, Gurugram, over a period of 2 years from January 2017 to January 2019. Patients were taken from both sexes and all age groups from different units of surgery. A total of 100 patients were taken for study who underwent cholecystectomy. Results: Mean age of patients in our study was 38.64 years. Most patients were females. Procedure adopted was open in 18% patients and lap cholecystectomy in 74% patients. Conversion from laparoscopic to open was done in 8% patients. In 8% patients there were operative complications. Average hospital stay was much less for lap cholecystectomy. Conclusions: After the advent of laparoscopic cholecystectomy, most of the surgeons are performing more and more of laparoscopic cholecystectomy. Here incision is small, pain is less, and hospitalization is shorter. Even in acute cholecystitis, in experienced hand, lap cholecystectomy can be performed safely. The author’s inclination is totally in favour of lap cholecystectomy, except the cases where lap cholecystectomy is contraindicated.